ПОЛІПШЕННЯ ЕЛЕКТРОМАГНІТНОЇ СУМІСНОСТІ ДЖЕРЕЛ ЖИВЛЕННЯ ДЛЯ СИСТЕМ КОНТАКТНОГО ЗВАРЮВАННЯ - Сафронов, П.С.; Бондаренко, Ю.В.; Бондаренко, О.Ф.; Сидорець, В.М.; Кучеренко, Д.В. (Інститут електродинаміки НАН України, Київ, 2014)
Energy Storage circuit topology with multiphase interleaved power factor corrector is proposed to use for increasing electromagnetic compatibility of power supplies for resistance welding with power line. The offered power factor corrector realization way means operation of each unified phase in discontinuous current mode that is near to boundary mode. It makes possible to provide approximately sinusoidal input current. The estimation of total harmonic distortion is carried out and the efficiency of proposed decisions is confirmed by simulation. References 6, figures 4.